Comparison of Secondary Geometry Syllabus Being Taught in India and the United States of America - Jaiswal, Shilpa; Amin, Shabnam (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Mathematics is plays an important role in human life. It is a tool which helps us to understand the world around us and with the knowledge of math humans make the world a better place to live. Geometry is one of the most important branches of mathematics which helps us to visualise different relations and wonderful properties of figures and shapes. It helps to critically analyse the given information and retrieve visual pattern and calculate some concrete information about that figure and shape. It teaches the inductive and deductive reasoning to form definitions, axioms and theorems. Geometry starts from conception of a human life till its death. It is involved in every aspect of human life. A doctor checks the dimension of an embryo and compares it with a healthy embryo‘s size. The moment a child is born Geometry enters into its life automatically. Doctors use Geometry to decide if it‘s a healthy baby. Within a few months‘ baby learns to identify different shapes and objects and learns the meaning of it. As the child grows older the whole life starts revolving around Geometry. Geometry is used in architecture to design buildings‘ shape and their blueprints. Robotics, and video games use Geometry to simulate 3D images in virtual world. GPS uses geometry to give the correct location. Geography uses Geometry to calculate the location, trajectories of different stars. Medical profession uses it for CT scans, MRIs for diagnosis and treatment of different diseases. Educationist use it to increase student achievement. Real world used a lot of Geometry to decide angles between the blades of a fan, track length of a circular ground, how much paint is needed for a wall, what should be the angle of a ramp to make it easier for disabled person, translation in a game of chess, dilation while making copies or printouts, rotation in revolving door, reflection in symmetric images, making miniatures of bigger objects, using congruent and similar triangles while constructing homes, line and segments that intersect circles in bicycle chain. The current paper is an attempt to find the topics covered in Geometry in two different countries. In this paper researchers tried to explore the syllabus of Geometry being taught at secondary level in two different countries- India and the United States. This paper explored the similarities and differences in Geometry taught at secondary level in these countries. Findings suggested some significant differences and a lot of similarities in topics being taught. This was a qualitative study to compare and figure out the quality of Geometry being taught.